2016
DOI: 10.1111/acer.13284
|View full text |Cite
|
Sign up to set email alerts
|

Partial Protection by Dietary Antioxidants Against Ethanol‐Induced Osteopenia and Changes in Bone Morphology in Female Mice

Abstract: Background Chronic alcohol consumption leads to increased fracture risk and an elevated risk of osteoporosis by decreasing bone accrual through increasing osteoclast activity and decreasing osteoblast activity. We have shown that this mechanism involves the generation of reactive oxygen species (ROS) produced by NADPH oxidases (NOX). It was hypothesized that different dietary antioxidants, N-acetyl cysteine (NAC, 1.2mg/kg/d) and α-tocopherol (VitE, 60 mg/kg/d)) would be able to attenuate the NOX-mediated ROS e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 62 publications
6
23
0
1
Order By: Relevance
“…Our results did not show an increase in the inflammatory marker CRP in subjects with the highest PEth values. Our finding that alcohol consumption was positively associated with oxidative stress (via increased 4‐HNE) agrees with previously reported mechanisms of alcohol (Alund et al., ; Ronis et al., ). However, these changes were modest and not correlated with osteocalcin.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results did not show an increase in the inflammatory marker CRP in subjects with the highest PEth values. Our finding that alcohol consumption was positively associated with oxidative stress (via increased 4‐HNE) agrees with previously reported mechanisms of alcohol (Alund et al., ; Ronis et al., ). However, these changes were modest and not correlated with osteocalcin.…”
Section: Discussionsupporting
confidence: 93%
“…Our measures would not be able to detect bone‐localized oxidative stress, and this could be the underlying cause of the suppressed osteocalcin secretion by osteoblasts. Suppressed osteocalcin is consistent with NADPH oxidase‐dependent ROS production observed in bone from rodents exposed to EtOH in vivo, and in mesenchymal stem cells and osteoblasts exposed to EtOH in vitro (Alund et al., ; Chen et al., ; Watt et al., ).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Heavy alcohol consumption increases bone marrow adiposity in growing rodents (Alund et al., ; Howe et al., ; Maddalozzo et al., ; Maurel et al., 2012b), a response observed in the present study in young adult male rhesus macaques. Osteoblasts and bone marrow adipocytes originate from the same bone marrow mesenchymal stem cells, and in vitro studies suggest that, at high concentrations, alcohol decreases osteoblast number by modulating the differentiation program of stem cells to form adipocytes at the expense of osteoblasts (Chen et al., ; Wezeman and Gong, ).…”
Section: Discussionsupporting
confidence: 63%
“…Tissue morphology not only verifies the results of bone mass detection but also shows the conditions of osteoblasts, osteoclasts, bone cells, and marrow cavities in a more intuitive way 22,23 . The results of this study showed that the microstructure and morphology of bone trabecula in model rats were damaged to different degrees, which is consistent with previous reports 24,25 . The results showed that microstructure and bone tissue morphology were significantly improved through AAT with TGP, confirming the effectiveness of AAT with TGP and provided experimental evidence for its clinical application in PMOP.…”
Section: Bone Morphology Changessupporting
confidence: 93%